Summary of Efficiency and productivity differential effects of the land certification program in Ethiopia - Ghebru, Hosaena; Holden, Stein (International Food Policy Research Institute, 2014)
Although theory predicts that better property rights to land can increase land productivity through tenure security effects (investment effects) and through more efficient input use due to enhanced tradability of the land (factor intensity effect), empirical studies on the size and magnitude of these effects are very scarce. Taking advantage of a unique quasiexperimental survey design, this study analyzes the productivity impacts of the Ethiopian land certification program by identifying how the investment effects (technological gains) would measure up against the benefits from any improvements in input use intensity (technical efficiency). For this purpose, we adopted a data envelopment analysis–based Malmquist-type productivity index to decompose productivity differences into (1) within-group farm efficiency differences, reflecting the technical efficiency effect, and (2) differences in the group production frontier, reflecting the long-term investment (technological) effects.